A novel Compound Elliptical-type Concentrator for parabolic primaries with tubular receiver. (September 2016) - Canavarro, Diogo; Chaves, Julio; Collares-Pereira, Manuel
Highlights: The paper presents a CEC-type concentrator for tubular receivers. The paper compares the new optics with a Parabolic Trough and with a XX SMS. The comparison method uses the same size receiver and the same acceptance. The paper presents a complete solar field analysis for each concentrator. Abstract: The Parabolic Trough (PT) is the most used concentrator in CSP (Concentrated Solar Power). However, this concentrator technology is facing a significant challenge to increase its overall efficiency and cost-effectiveness. Meanwhile, other low-cost solutions such as Fresnel concentrators are also being perceived as potentially attractive. In order to achieve the lower cost goal, new optical solutions can be considered, in parallel with improvements coming, for instance, through the use of new materials or manufacturing solutions. But conventional PTs can still be improved to yield, for instance, higher concentration values, a possible starting point for higher conversion efficiency. These new solutions, in turn, can also be useful for other technologies and applications (Fresnel Concentrators, Central Tower Receivers, etc.). However it is easier to develop and test these solutions in conjunction with parabolic primaries (continuum primary). And that is the topic of this paper: to present a new Compound Elliptical-type Concentrator for a parabolic primary with a tubular receiver. A comparison is made between this new concentrator and two other concentrators (a conventional PT concentrator and a XX SMS (Simultaneous Multiple Surface) concentrator), as well as a calculation of the total amount of collected energy (kW h) for a particular location, Faro (Portugal). The paper ends with a discussion of the results obtained, their impact and possible applications in the future.